EVALUATION OF PUBLIC SERVICES PROVIDED BY THE INTELLIGENCE AND SECURITY UNIT REGARDING THE ISSUANCE OF POLICE CLEARANCE CERTIFICATES (SKCK) AT THE MAKASSAR CITY POLICE DEPARTMENT - Muthia Fadya Azzahra S; Andi Cudai Nur; Herlina Sakawati (Universitas Negeri Makassar, 2026)
This research aims to find out how public services are created in the SKCK processing process and to find out the supporting and inhibiting factors for creating public services in the SKCK processing process at the Makassar Police Intelligence and Security Unit. This research uses a qualitative approach and produces descriptive data. Data collection was used using observation, interviews and documentation techniques. Data analysis techniques use Miles Huberman, namely, data condensation, data presentation, and drawing conclusions. The results of this research show that the Intelligence and Security Unit's Public Service Evaluation of Making Police Record Letters (SKCK) for the Makassar City Police. There are 2 stages of the SKCK making service, namely offline (coming to the police station) and online by accessing the National Police Precision APP application, which, like the making stages, requires different time periods. The additional administrative requirements for making a Skck are that the BPJS card must be active for the Skck applicant who takes care of it. This rule will be implemented starting March 1 2024. However, Skck applicants do not yet know the rules. issued so that there are obstacles such as checking that the applicant's BPJS card is inactive or has not paid so that the applicant's SKCK cannot be issued. Applicants/people who administer SKCK prefer the online method because they can access it from various places and conditions. And the facilities and infrastructure provided are not yet fully effective. Sat Intelkam proposes to increase new sustainable breakthroughs by promoting the creation of Skck Online on social media, providing mobile Skck services so that people do not have difficulty reaching them from where they live.